Expression of citrulline and homocitrulline residues in the lungs of non-smokers and smokers: implications for autoimmunity in rheumatoid arthritis - Lugli, E; Correia, R; Fischer, R; Lundberg, K; Bracke, K; Montgomery, AB; Kessler, B; Brusselle, G; Venables, P (BioMed Central, 2015)
Smoking is a well-established risk factor for rheumatoid arthritis (RA), and it has been proposed that smoking-induced citrullination renders autoantigens immunogenic. To investigate this mechanism, we examined human lung tissue from 40 subjects with defined smoking status, with or without chronic obstructive pulmonary disease (COPD), and control tissues from other organs for citrullinated proteins and the deiminating enzymes peptidylarginine deiminase type-2 (PAD2) and -4 (PAD4).Lung tissue samples, dissected from lobectomy specimens from 10 never smokers, 10 smokers without airflow limitation, 13 COPD smokers and eight COPD ex-smokers, and control tissue samples (spleen, skeletal muscle, liver, ovary, lymph node, kidney and heart), were analysed for citrullinated proteins, PAD2 and PAD4 by immunoblotting. Citrulline and homocitrulline residues in enolase and vimentin were analysed by partial purification by gel electrophoresis followed by mass spectrometry in 12 of the lung samples and one from each control tissues. Band intensities were scored semi-quantitatively and analysed by two-tailed Mann-Whitney T-test.Within the lung tissue samples, citrullinated proteins, PAD2 and PAD4 were found in all samples, with an increase in citrullination in COPD (P = 0.039), but minimal difference between smokers and non-smokers (P = 0.77). Citrullination was also detected at lower levels in the tissues from other organs, principally in lymph node, kidney and skeletal muscle. Mass spectrometry of the lung samples showed that vimentin was citrullinated at positions 71, 304, 346, 410 and 450 in non-smokers and smokers both with and without COPD. A homocitrulline at position 104 was found in four out of six COPD samples and one out of six non-COPD. Citrulline-450 was also found in three of the control tissues. There were no citrulline or homocitrulline residues demonstrated in α-enolase.We have shown evidence of citrullination of vimentin, a major autoantigen in RA, in both non-smokers and smokers. The increase in citrullinated proteins in COPD suggests that citrullination in the lungs of smokers is mainly due to inflammation. The ubiquity of citrullination of vimentin in the lungs and other tissues suggests that the relationship between smoking and autoimmunity in RA may be more complex than previously thought.